Peran Mediasi Customer Satisfaction dalam Customer Experience Dan Loyalitas Pelanggan - Demak Claudia Yosephine Simanjuntak; Purnama Yanti Purba (University of Merdeka Malang, 2020)
This study aims to examine the effect of customer experience and customer satisfaction on customer loyalty and whether customer satisfaction mediates the relationship between customer experience and customer loyalty. The data analysis method used is structural equation modeling-partial least squares (SEM-PLS). The number of respondents is 150 people. Sampling technique of this study is quota sampling method. The study shows that customer experience has a positive and significant effect on customer loyalty, customer experience has a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty. By conducting mediation testing, it is concluded that customer satisfaction is significant as a mediator of the relationship between customer experience and customer loyalty.